The Role of the Regulations in Indonesia State System - Rokilah Rokilah (Ajudikasi : Jurnal Ilmu Hukum, 2020)
In the current era of globalization, when national borders are no longer clear, the existence of written law (jus scriptum), especially in the field of legal studies, namely legislation, has become a basic human need in efforts to achieve justice, peace and legal certainty. Based on the background of the problem, the formulation of the problem is: 1) how the role of legislation in the Indonesian constitutional system; 2) the function of legislation in the formation of national law. This study uses normative juridical research methods that are qualitative in nature. The data source used is secondary data sources, while the method of collecting data in researching research objects is library data obtained through library research. The results of this study illustrate that the role of legislation is increasingly important as a claim for the principle of legality as one of the characteristics of the rule of law, and the function of legislation confirms that the laws and regulations contain government policies primarily as a means of legitimacy for the government to run the government.